THEORIES OF LEARNING AND DEVELOPMENT OF INFORMATION TECHNOLOGIES - WALAT, Wojciech (Trends in education, 2010)
The search of uniform theory, without regard multi-directions of the man's psyche be convicted on failure. All man's conceptions emphasize one be his essence's several dimensions. Therefore for more far connected from search in range the optimum solutions analyses the modellings and optimization the hypermedia didactic programms one should to accept their didactic complementariness and methodical depending on mutual being complementary to one another the individual conceptions as well as methods and forms of pedagogical conduct.
Keywords: theories of learning; information technology.